Wpływ metod trzebieży na wskaźniki przewagi konkurencyjnej drzew dorodnych w jednowiekowych drzewostanach sosnowych II i III klasy wieku - Zachara, Tadeusz (Leśne Prace Badawcze, 2014)
The research aim was to evaluate the influence of different thinning methods on future crop tree growth. Investigations were conducted on permanent Scots-pine experimental plots, established in 1960s and 1970s in Kozienice, Łąck, Parciaki and Janów Lubelski Forest Districts. To assess the response to thinning of future crop trees, their dominance coefficients were used. These are defined as quotients for each given future crop tree diameter and average stand diameter (WP1), the average dominant layer diameter (WP2) and the average diameter of 100 thickest trees per hectare (WP3). The difference between each coefficient value at the beginning and at the end of the measurement period was used as a measure of the thinning effect. On Kozienice, Łąck and Parciaki plots the differences between treatments were significant, especially in the period after first thinning. The increase of WP3 coefficient occurred in a case of strong thinning – TS1 and TS2. On plot Parciaki also the moderate thinning TU1 and TU2 had a significant influence on change of this coefficient. On plot Janów Lubelski the influence of treatment has not been stated in the first 5-year period but in the next one. Analyses of changes in the dominance coefficients confirmed the hypothesis that the WP3 coefficient is very useful as it is the most stable indicator of future crop-tree position in a stand. On Kozienice, Łąck and Parciaki plots the significant differences between treatments were stated, especially in the period after first thinning. The influence of thinning treatment on the plot Janów Lubelski was not considered for the first 5-year period but in the next one. All reactions to thinning were slower on this plot, possibly because of the relatively poor site conditions. This was a long-term effect. The results obtained suggest that very intense thinning of Scots pine stands should only be implemented under a restricted set of conditions – in healthy, not neglected, forest stands. Classical moderately-selective thinning is preferable to intense thinning and is the most convenient option for pine stands.